ASPECTS OF THE FUNCTIONING OF SHELTERED WORKSHOP (Research Bulletins of the Faculty of Economic Sciences, 2018)
The article presents the conditions needed for gaining the status of the Supported Employment Enterprise, including its powers and duties, as well as the Supported Employment Enterprise as a taxpayer, co-financing salaries, and exemption from fees. Its purpose is to assess the impact of economic aspects on the functioning of the Supported Employment Enterprise. The article was prepared on the basis of professional literature, numerous enactments and economic analysis.
Keywords: disabled person, level of disability, Supported Employment Enterprise, statutory privileges, State Fund for Rehabilitation of Disabled People, economic efficiency.